The Influence of Social Media Platforms on Writing Skills for Students in Foreign Language Learning in Higher Education - Henny Noviany; Evie Farida Juliarta; Deasy Sandya; Dahlan Abdullah (International Journal of Language and Ubiquitous Learning, 2023)
Background. In the era of foreign language learning in the 21st century, where society is increasingly connected through technology, social media has become a crucial aspect that plays a role in developing students' writing skills. Society 5.0, which focuses on digital connectivity, has had a significant impact on the learning paradigm, raising questions about the influence of social media as a learning tool. Social media, such as Facebook, Twitter, and Instagram, provide a digital environment rich in information and language interaction. Purpose. This research aims to better understand the complexity of the relationship between social media and students' writing skills in the context of foreign language learning in higher education. Through a quantitative approach using survey methods, this research can provide an in-depth understanding of social media usage patterns and their impact on students' writing skills. Method. This research applies survey and questionnaire methods to measure the impact of social media use on foreign language students' writing skills, with a focus on Arabic and English. The research sample involved 40 students, and data analysis used the Miles and Huberman method to understand the relationship and impact. Results. Participation in forums or foreign language groups on social media shows that students use these platforms as a forum for communicating, exchanging information, and discussing learning topics. As many as 100% of respondents had participated in such forums, indicating high student interest in collaborative activities via social media. As many as 36 out of 40 respondents felt that social media had influenced their formal writing style. These influences can range from adaptations to sentence structure to word choice, creating variations in formal writing style. Conclusion. Research shows that the majority of students (32 respondents) agree that social media can be an effective learning tool in foreign language learning. However, 8 respondents stated they were neutral, showing variations in perceptions of the effectiveness of social media as a learning tool.